The implications of digital estate in shariah compliant Fintech: a legal analysis - Omoola, Sodiq; Oseni, Umar Aimhanosi; Kamal, Hafsat Ibrahim (2020)
The surge in shariah compliant fintech has continued to create large volume, value and scale of intangible digital assets across platforms. This paper provides a legal analysis for digital estates in shariah compliant fintech environments. The paper adopts qualitative analysis of both primary and secondary sources from existing journals and regulatory instruments in Islamic finance jurisdictions to explore the gaps in the law regarding digital estate and unclaimed money regulation. The paper further compares different legal approaches adopted by other jurisdictions in regulating digital estate. The paper finds that there is a scope for administration of digital estate in both regulated and unregulated shariah compliant fintech platforms. Similarly, the adoption of e-KYC which complies with shariah ethos is essential to ensure that digital estate is not lost upon the demise of the account holder. The legal right and title of the account holder and legal heirs can only be protected through the operation of digital estate regulation in a Shariah-compliant fintech environment. Similarly, this paper is of value to successor and administrators of account holders in fintech environments as recommends measures to uphold the property rights and financial benefit of the account holders and legal heirs.